Desempenho do concreto frente a adições de Spray Dryer Ash na usina termelétrica do Pecém - Santana, Raphael Arlego de Alcântara (2018)
After the flue gases from a thermoelectric plant that uses coal as combustive passes through a dessulfurizator, the fly ashes get mixed with sulphurous products, hampering the use of this residue. A possible use for this ash, named spray dryer ash (SDA), is as a mineral addition to concrete. The objective of this paper is to evaluate the performance of concrete with addition of different percentages of spray dryer ash from Pecém's thermoelectric plant. Concrete specimens with 0%, 5%, 10% and 20% of SDA addition to the cement mass were cast and had its compressive strength measured. After that a sulfur attack was made to evaluate the volumetric change, a concern when working with sulfur-containing compounds in concrete. It is concluded that an addition of 20% of SDA can raise the compressive strength of concrete without worrying about sulfate attacks, while a 5% or a 10% addition behaves similar to a concrete without SDA.